Jackknife empirical likelihood test for mean residual life functions. Issue 7 (3rd April 2017) - Chen, Ying-Ju; Ning, Wei; Gupta, Arjun K.
ABSTRACT: Mean residual life (MRL) function is an important function in survival analysis which describes the expected remaining life given survival to a certain age. In this article, we propose a non parametric method based on jackknife empirical likelihood through a U -statistic to test the equality of two mean residual functions. The asymptotic distribution of the test statistic has been derived. Simulations are conducted to illustrate the performance of the proposed test under different distributional assumptions and compare with some existing method. The proposed method is then applied to two real datasets.